Diet for draft dodgers - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1996)
Farmers in semi-arid West Africa could get more work out of their oxen simply by slightly modifying the way they manage their animals, according to a recent report from the Centre for Tropical Veterinary Medicine (CTVM), Edinburgh, UK and the...